Elastocaloric Performance of Natural Rubber: The Role of Nanoclay Addition - Marica Bianchi; Luca Fambri; Mauro Bortolotti; Alessandro Pegoretti; Andrea Dorigato (Molecules, 2025)
This work investigates the effect of nanoclay addition—specifically natural montmorillonite (MMT) and organo-modified montmorillonite (O-MMT)—on the elastocaloric performance of natural rubber (NR), a promising material for solid-state cooling due to its non-toxicity, low cost, and ability to exhibit large adiabatic temperature changes under moderate stress (~a few MPa). Despite these advantages, the cooling efficiency of NR remains lower than that of conventional vapor-compression systems. Therefore, improving the cooling capacity of NR is essential for the development of solid-state cooling technologies competitive with existing ones. To address this, two series of NR-based nanocomposites, containing 1, 3, and 5 phr nanofiller, were prepared by melt compounding and hot pressing and characterized in terms of morphology, thermal, mechanical, and elastocaloric properties. The results highlighted that the better dispersion of the organoclays within the rubber matrix promoted not only a better mechanical behavior (in terms of stiffness and strength), but also a significantly enhanced cooling performance compared to MMT nanofilled systems. Moreover, NR/O-MMT samples demonstrated up to a ~45% increase in heat extracted per refrigeration cycle compared to the unfilled NR, with a coefficient of performance (COP) up to 3, approaching the COP of conventional vapor-compression systems, typically ranging between 3 and 6. The heat extracted per refrigeration cycle of NR/O-MMT systems resulted in approx. 16 J/cm3, higher with respect to the values reported in the literature for NR-based systems (ranging between 5 and 12 J/cm3). These findings emphasize the potential of organoclays in enhancing the refrigeration potential of NR for novel state cooling applications.